Early surgical ligation versus a conservative approach for management of patent ductus arteriosus that fail to close after indomethacin treatment - Jhaveri, Nami (2010)
OBJECTIVE: To examine whether a more conservative approach to PDA treatment is associated with an increase or decrease in morbidity compared with an approach of early PDA ligation. STUDY DESIGN: In 1/2005 we changed our approach to infants (≤27 weeks gestation) that failed indomethacin treatment. We changed from an early surgical approach (where feedings were stopped and all PDAs were ligated)(Period 1:1/99-12/04, n=216) to a more conservative approach (feedings continued and PDAs were ligated only if cardiopulmonary compromise developed)(Period 2:1/05-8/09, n=180). All infants in both periods received prophylactic indomethacin. RESULTS: The two periods had similar rates of perinatal/neonatal risk factors and indomethacin failures (24%); ventilator management and feeding advance protocols also were similar between the two periods. The conservative approach was associated with decreased rates of ductus ligation (72% versus 100%, p<0.05). Even though infants were exposed to larger PDA shunts for longer durations in the conservative treatment period, the rates of BPD, Sepsis, ROP, Neurological Injury, and Death did not change; their overall rate of NEC was significantly lower. CONCLUSIONS: These findings support the need for new controlled, randomized trials to reexamine the benefits and risks of different approaches to PDA treatment.